A TINJAUAN KONSISTENSI AJARAN ISLAM DALAM QS. AL – BAQARAH AYAT 173 DALAM PERSOALAN VAKSIN MR: TINJAUAN KONSISTENSI AJARAN ISLAM DALAM QS. AL – BAQARAH AYAT 173 DALAM PERSOALAN VAKSIN MR - Lenny Herlina (Schemata: Jurnal Pasca Sarjana IAIN Mataram, 2019)
Islam regulates all aspects of human life, including the order of life on earth in order to lead to happiness in the world and the hereafter. One of the supports for this happiness is having a healthy body, making it possible for us to worship better to God. Islam strongly emphasizes health, physically and mentally and it is the second pleasure after the Faith. Health is a human right and something that is in accordance with human nature, so all the paths that can lead to health are worth taking, as long as it does not conflict with Islamic teachings. This paper aims to show how Allah SWT has given a middle way between an obligation and a need, in order to achieve harmony between something that he forbids and then permits through clarification of science. To make it easier, in this paper I raise one of the latest health topics which is a debate over the pros and cons, namely the use of the Measles Rubella (MR) vaccine because it contains an unclean / haram element. The research method that I used was qualitative research with literature technique as one of the forms of approach to religious research, while the book I studied was the Holy Qur'an al-Baqarah verse 173, the Technical Manual and Vaccine Campaign of the MR Directorate General of P2P Ministry of Health RI, 2017 and MUI Fatwa Number: 33 of 2018 Concerning the Use of Mr (Measles Rubella) Vaccine Products From SII (Serum Institute Of India) For Immunization.